Evaluation and Optimization of Genomic DNA Extraction from Food Sample for Microfluidic Purpose. Issue 1 (February 2020) - Afnan Uda, M. N.; Parmin, N. A.; Jambek, Asral Bahari; Hashim, U.; Uda, M. N. A.; Shaharuddin, S. N. A.
Abstract: Contamination of various food samples became one of the critical issues in food pathogen infection. Food pathogen can be detected by using digital polymerase chain reaction (PCR) and sequencing. These methods were reliable but consuming and take a longer time for detection. The present work describes the innovation to develop a technology to extract double-stranded deoxyribonucleic acid (dsDNA) from food samples and then denatured dsDNA into and single-strand DNA (ssDNA) for further use on the chip using microfluidic device. Microfluidic device is a lab-on-chip device that consist of microfluidic channels that provide paths for biomolecules to flow to individual point of care. DNA extraction is the process by which DNA is separated from proteins, membranes, and other cellular material contained in the cell from which it is recovered. Lysis solution is used in the process of extraction the DNA to break up the cells containing DNA from protein and other cellular materials. This extraction firstly be done in the most labour-intensive in obtaining the DNA biomolecules. Extraction methods may require an overnight incubation, may be a protocol that can be completed in minutes or a couple of hours by using a commercial kit. The disadvantages of the laboratory and commercial kit is due to time-consuming, poor cost-effectiveness, the need to use big laboratory and a complicated process which need an expertise to conduct the experiment and interpret the data. This research is proposed to design and fabricate a microfluidic device that has DNA extraction capabilities. In this research DNA extraction using a commercial kit will be used as a comparison for the quality of the result. The microfluidic device can be used in health care delivery system and will help the doctors in diagnostic process to identify disease of a patient rapidly. Other than that, the output extracted from microfluidic device will be used for DNA probe target interaction for diagnostic kit. The major advantage of microfluidic device is that it consumes less time compared to the conventional chemical methods.